PERANCANGAN MESIN SPOT WELDING PORTABLE UNTUK SKALA LABORATORIUM - Irna Sari Maulani; Heris Syamsuri; Ade Kurniawan (Universitas Widyatama, 2024)
Specifically used to connect plates. A high electric current is applied to the material that is squeezed through the electrodes during the pressing process by the two electrodes. Spot Welding is widely used in the industrial world both large and small scale. In large industries, spot welding has a solid and fixed design, meaning that the method of placement has been determined in a special place and if you want to move it, you have to use heavy equipment. Whereas for small-scale spot welding it is urgently needed for thin plate processing, but the price and shape which are difficult to move certainly require innovation so that the needs of small industries can be fulfilled. In the manufacturing process course in the Mechanical Engineering Study Program, Faculty of Engineering, Galuh University, there is welding material and practice, of course, to achieve maximum learningoutcomes in welding practice, it is necessary to make a portable spot welding equipment. From the discussion above, the authors are interested and inspired to design a portable spot weld machine for the laboratory scale, starting with drawing, planning, sketching or assembling several separate elements into a single unit that is used to describe tools using solidwork applications and the Finite Element Method (FEM) or commonly called Finite Element Analysis (FEA) as an analysis tool. The method used in the design process for portable spot welding machines is made using Solidwork software. The design dimensions of the spot welding machine are 63 cm long, 14 cm wide, 14 cm high. The dimensions of the pedal that has been made are 10 cm long, 38 cm wide and 98 cm high. Electrical specifications require 700-800 watts of power, 220 volts, 5 amperes electric current. The design analysis that has been carried out is divided into stress analysis which has a value of 2,476,233N/m2, while the yield stress of the ASTM A36 material is 250 MPa so that the frame is declared safe. Displacement and strain analysis produces a value of 0 and safety of factor analysis produces a value of 101.